DD-017 Thefts of medicines from hospital pharmacies: A european challenge. (14th February 2016) - Turchetti, G; Pani, M; Cannizzo, S; Antonel, A; Rossi, E
Abstract : Background: Fake medicines, causing health damage to patients, economic losses to the National Health Systems, and economic and reputational damage to pharmaceutical companies represent at least 6% and 10% of the global and European pharmaceutical markets, respectively. Purpose: Main objectives: increase awareness of drug theft in hospital top management, develop a new model for the effective management of the safety dimension of hospital pharmacies (HPs), and diffuse the culture of prevention, safety and risk management. Specific objectives: develop 'guidelines' for assessing and increasing the safety level of HPs. Material and methods: During the years 2014 and 2015, a sample of 30 HPs were visited and their level of safety assessed. The selected HPs belonged to different geographical regions and had various dimensions: small (HPs in hospitals with <500 beds), medium (500–1000 beds), large (>1000 beds or centralised warehouses). A security risk score was assigned to each HP, synthesising the overall coverage degree based on the combined assessment of 5 protection criteria: (i) entrances control; (ii) volumetric protection detectors; (iii) passive perimeter protection systems for windows/walls, active protection systems; (iv) alarm transmission devices; and (v) video recording systems. Results: Both lack of planning for security risk assessment and poor application of protective systems were observed. Only 10% of the sample satisfied the first three security criteria and had a sufficient security risk level; 66% of the sample were inadequate (few criteria partially satisfied); 24% of the sample were seriously insufficient (both basic passive and active protection systems were missing). Based on this risk assessment activity, guidelines have been produced containing examples of best practice and guiding principles for effectively assessing the security risk level of HPs. Beneficiaries are hospital decision makers and managers, HP managers and HP personnel. Conclusion: The paper presents data of the first national study that has assessed (through accurate on-site visits) the security of HPs, and proposed a tool (specific guidelines) for assessing and increasing the safety level of HPs. The main limitation of the study may be the relatively small number of HPs analysed. The study confirms the high vulnerability of HPs and the urgency for strong action for promoting diffusion of the risk management culture. References and/or Acknowledgements: Trancrime, 2014 No conflict of interest.